2015
DOI: 10.1089/pho.2014.3854
|View full text |Cite
|
Sign up to set email alerts
|

Blue Laser Inhibits Bacterial Growth of Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa

Abstract: Objective: The purpose of this study was to analyze the influence of blue laser on bacterial growth of the main species that usually colonize cutaneous ulcers, as well as its effect over time following irradiation. Background data: The use of blue laser has been described as an adjuvant therapeutic method to inhibit bacterial growth, but there is no consensus about the best parameters to be used. Methods: Strains of Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 27853, and Escherichia coli ATCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 24 publications
1
48
0
3
Order By: Relevance
“…de Sousa analyzed the influence of aBL emitted from a blue laser on the bacterial growth of S. aureus, P. aeruginosa, and E. coli (de Sousa et al, 2015b). Bacterial suspensions were exposed to a single exposure of a 450-nm blue laser at varying radiant exposures from 0 to 24 J/cm 2 .…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…de Sousa analyzed the influence of aBL emitted from a blue laser on the bacterial growth of S. aureus, P. aeruginosa, and E. coli (de Sousa et al, 2015b). Bacterial suspensions were exposed to a single exposure of a 450-nm blue laser at varying radiant exposures from 0 to 24 J/cm 2 .…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…de Sousa et al investigated the effect of blue light emitted from a laser (λ = 450 nm; 70 mW) on strains of S. aureus [25]. Growth was inhibited at fluences higher than 6 J/cm 2 (reduction of 22% for 6 J/cm 2 ; no higher inhibition rates detected for 12, 18 and 24 J/cm 2 ; no antibacterial effect [53] in any case).…”
Section: Staphylococcus Sppmentioning
confidence: 99%
“…Guffey and Wilborn reported that the irradiation with a 405 nm blueviolet laser had a bactericidal effect against S. aureus and Pseudomonas aeruginosa [27]. Other studies also reported that visible light is effective against Porphyromonas gingivalis, Fusobacterium nucleatum, Staphylococcus aureus, Streptococcus mutans, and Escherichia coli [28,29]. The results of our previous study also confirmed that the irradiation with a 405 nm blue-violet laser had a bactericidal effect against P. gingivalis which is a major periodontopathogenic microorganism as well as Prevotella intermedia, and even against Candida albicans which is a major responsible fungus causing candidiasis [30].…”
Section: Introductionmentioning
confidence: 98%